2015
DOI: 10.1140/epjds/s13688-015-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey of results on mobile phone datasets analysis

Abstract: In this paper, we review some advances made recently in the study of mobile phone datasets. This area of research has emerged a decade ago, with the increasing availability of large-scale anonymized datasets, and has grown into a stand-alone topic. We survey the contributions made so far on the social networks that can be constructed with such data, the study of personal mobility, geographical partitioning, urban planning, and help towards development as well as security and privacy issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
411
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(435 citation statements)
references
References 175 publications
3
411
0
6
Order By: Relevance
“…The main difference between our work using Wi-Fi cloud data and other works based on cellular mobile data, is that our dataset corresponds to a local scale network (e.g., restaurants, malls etc. ), whereas datasets from cellular mobile networks focus on larger aggregation scales (wide area, metropolitan, nationwide) -see [11] and [5] for surveys. Consequently, we expect that our dataset can capture other kinds of mobile usage behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between our work using Wi-Fi cloud data and other works based on cellular mobile data, is that our dataset corresponds to a local scale network (e.g., restaurants, malls etc. ), whereas datasets from cellular mobile networks focus on larger aggregation scales (wide area, metropolitan, nationwide) -see [11] and [5] for surveys. Consequently, we expect that our dataset can capture other kinds of mobile usage behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned numbers prove the satisfactory representativeness of the dataset to describe the entire population distribution dynamics, assuming that the mobile device distribution and motion dynamics patterns of large mobile communication companies matches quite well with the population distribution and motion dynamics patterns (see also Section 7). Wesolowski et al [24], Frias-Martinez et al [25] and Blondel et al (2015) [19] have observed that differential mobile ownership biases do not seem to have much effect on mobility patterns within particular regions. This suggests that the social bias of the clients of certain providers is a diminishing issue mainly because of highly competitive mobile services market and attractive packages.…”
Section: Population and Mobility Data Collection Methods-data And Govmentioning
confidence: 98%
“…Among others, a good overview of the results of mobile phone datasets is presented in Blondel et al [19], where the authors question the suitability of the mobile data, e.g., they argue that datasets are noisy and some links appear there by chance, while others have not been captured. It would thus be interesting to question the stability of the obtained results, provided that the real network is different from what has been observed in the data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of always being with their owners, mobile phones provide detailed maps of users' lives and have become a valuable tool in computational social science research (4). Data from phones-specifically where people are-is being used to map people's movements during a disaster (5), to learn how to halt the spread of infectious diseases (6), and so forth.…”
mentioning
confidence: 99%